Urgensi Peraturan Daerah DIY Nomor 1 Tahun 2024 Tentang Ekonomi Hijau Dalam Mencapai Pembangunan Berkelanjutan - Mushtafa, Madinnatu Nava (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: Freen economy policies are commonly framed as administrative responses to global sustainability agendas, this research argues that, in the context of Yogyakarta, the regulation represents a site of normative negotiation between state law and lived Islamic environmental ethics. Aims: This study examines the dialectical relationship between fiqh al-bi'ah and public policy through a socio-legal analysis of Regional Regulation of the Special Region of Yogyakarta Number 1 of 2024 on Green Economy within the framework of maqasid al-shari'ah. While green economy policies are commonly framed as administrative responses to global sustainability agendas, this research argues that, in the context of Yogyakarta, the regulation represents a site of normative negotiation between state law and lived Islamic environmental ethics. Method: Employing a socio-legal approach that integrates normative legal analysis with empirical fieldwork, this study analyzes legal documents alongside in-depth interviews and observations involving government officials, Islamic organizations, and local stakeholders. Finding: The findings reveal that the Regional Regulation functions as a hybrid legal product shaped by interactions among bureaucratic mandates, market interests, and religious moral discourses. Implication: Rather than formalizing Islamic law textually, the regulation internalizes principles of environmental stewardship aligned with hifz al-'alam through processes of localization and institutional adaptation. The case of policy implementation in Gunungkidul further demonstrates tensions between technocratic national indicators and socio-ecological local realities, highlighting the need for contextualized legal interpretation grounded in maslahah. Originality: This study contributes to the anthropology of Islamic law by demonstrating how fiqh al-bi'ah operates as lived law within regional governance structures, expanding contemporary discussions on Islamic environmental governance beyond doctrinal discourse toward institutional transformation.